Wet Chemical Method ZnF2 Interlayer for High Critical Current Density Lithium Metal Batteries Utilizing Ba and Ta–Doped Li7La3Zr2O12 Garnet Solid Electrolyte - Subhajit Sarkar; Vishnu Surendran; Venkataraman Thangadurai (Advanced Materials Interfaces)
Abstract Li metal batteries with garnet‐type solid electrolytes have the potential to increase specific energy and power densities of current Li‐ion batteries. Li metal batteries have been hampered by the poor wettability of solid electrolyte with elemental lithium. Here, to resolve the solid garnet electrolyte/Li interface issue, a scalable, cost‐effective, and efficient surfactant‐assisted wet‐chemical strategy is developed. A ZnF2 interlayer coating is applied on Ba and Ta ‐co‐doped Li7La2.75Ba0.25Zr1.75Ta0.25O12 that formed LiF and Li‐Zn alloy upon contact with molten Li. Conformal contact applying a homogenous surfactant‐assisted ZnF2 coating reduced the interfacial resistance from 87 to 15.5 Ω cm2 which enhanced critical current density to a record high value of 5 mA cm−2 at room temperature. Dense and Li2CO3 free garnet solid electrolyte assisted in achieving long‐term stability for 1000 cycles at 1 mA cm−2. Interface stabilized Li/ZnF2‐ solid electrolyte/liquid electrolyte/LiFePO4 cell displayed a 90% capacity retention over 800 cycles at 0.2 C, with Coulombic efficiency of 99% as well as excellent cycle stability at 1 C, with ≈91% of capacity retention for 500 cycles. Using a new design principle for Li anode interfaces, next‐generation power‐intensive and stable solid‐state Li metal batteries can be developed.